Koheleth, the man and his world : a study of Ecclesiastes - Gordis, Robert, 1908-1992 (Schocken paperbacks., 1968)
The Biblical book of Koheleth (Ecclesiastes), which originated in the last centuries before the Christian era, is a basically heterodox if not an altogether heretical work. Above all, it is a profoundly human book. The unknown author has lost the faith of the Prophets in the victory of justice in the world and the belief that man can attain an understanding of the meaning of life. God does indeed exist, but his relation to the world and man is open to question. The gentle skeptic, sure only of his innate desire for happiness, calls upon man to accept the enjoyment that this transitory life affords. Ecclesiastes receives a thoroughgoing literary, philosophical and stylistic analysis, against the background of both Hebrew and Near Eastern Wisdom literature and in relation to Egyptian and Greek thought. The vocabulary and phraseology of the highly personal, whimsical, unconventional work leads the author to an appreciation of the character of the sophisticated anonymous writer: It is the style that is fundamental to the charm and perennial appeal of Koheleth. The scholarly reader will find, in addition, a new translation of, and a detailed commentary on, the work.